MacroH2A1 Regulation of Poly(ADP-Ribose) Synthesis and Stability Prevents Necrosis and Promotes DNA Repair - Ruiz, Penelope D. (Mol Cell Biol, 2019)
Through its ability to bind the ends of poly(ADP-ribose) (PAR) chains, the function of the histone variant macroH2A1.1, including its ability to regulate transcription, is coupled to PAR polymerases (PARPs). PARP1 also has a major role in DNA damage response (DDR) signaling, and our results show that macroH2A1 alters the kinetics of PAR accumulation following acute DNA damage by both suppressing PARP activity and simultaneously protecting PAR chains from degradation. In this way, we demonstrate that macroH2A1 prevents cellular NAD(+) depletion, subsequently preventing necrotic cell death that would otherwise occur due to PARP overactivation. We also show that macroH2A1-dependent PAR stabilization promotes efficient repair of oxidative DNA damage. While the role of PAR in recruiting and regulating macrodomain-containing proteins has been established, our results demonstrate that, conversely, macrodomain-containing proteins, and specifically those containing macroH2A1, can regulate PARP1 function through a novel mechanism that promotes both survival and efficient repair during DNA damage response.